THE TYPES AND FUNCTIONS OF SWITCHING AND MIXING CODES IN ENGLISH STUDENTS’ ONLINE DISCUSSIONS - Rejeki, Sri; Husna, Nida; Alek, Alek; Hidayat, Didin Nuruddin (Leksema: Jurnal Bahasa dan Sastra, 2023)
This study aims to discover the switching and mixing code types and their functions that are dominantly used in student online discussions. This research was designed in descriptive-qualitative method by using video recordings and interviews from Pragmatics class of postgraduate degree students as the data sources. The obtained data were then analyzed using Miles and Huberman model of analysis by involving data reduction, data display, and conclusion drawing. The results showed that students frequently switched and mixed codes during the discussions. In this case, ode mixing was dominantly occurred compared to code switching. There were 78 occurrences of code changes in total, with the proportions of 44 mixings and 34 switchings. Dealing with the types, insertion code mixing was found to be the mostly used in the discussions whereas intersentenential switching becomes the least. The phenomena of code switching and mixing in the classroom discussions has various functions, i.e.: for communication strategy, for delivering the meaning, for making clarification of the information, for defining specific terms, and for increasing understanding. This study also reflects the students' positive attitudes toward using switching and mixing codes in classroom discussion activities. It is recommended for further research to ensure the appropriate strategies for the teachers in switching and mixing codes for both offline and online classes.